Candida albicans enhances Staphylococcus aureus virulence by progressive generation of new phenotypes - Betsy Verónica Arévalo-Jaimes; Eduard Torrents (Current Research in Microbial Sciences)
Candida albicans and Staphylococcus aureus have been co-isolated from several biofilm-associated diseases, including those related to medical devices. This association confers advantages to both microorganisms, resulting in detrimental effects on the host. To elucidate this phenomenon, the present study investigated colony changes derived from non-physical interactions between C. albicans and S. aureus. We performed proximity assays by confronting colonies of the yeast and the bacteria on agar plates at six different distances for 9-10 days. We found that colony variants of S. aureus originated progressively after prolonged exposure to C. albicans proximity, specifically in response to pH neutralization of the media by the fungi. The new phenotypes of S. aureus were more virulent in a Galleria mellonella larvae model compared to colonies grown without C. albicans influence. This event was associated with an upregulation of RNA III and agrA expression, suggesting a role for α-toxin. Our findings indicate that C. albicans enhances S. aureus virulence by inducing the formation of more aggressive colonies. This highlights the importance of understanding the intricate connection between environmental responses, virulence and, fitness in S. aureus pathogenesis.